(untitled) (Przegląd Religioznawczy – The Religious Studies Review, 2026)
The article discusses the symbolic meaning of the cross in Western culture. Apart from its theological interpretation (saving people from sin and death), Christ’s cross can be understood as a metaphor for human fate, i.e. life as torment (the road to crucifixion) ending in a lonely death. At the same time, the cross has negative symbolism, visible from both a religious and secular perspective, i.e. the instrumentalization of suffering as a necessary sacrifice to be made in the name of God, Christ, the homeland, the nation and one’s neighbors. In religious terms, the cross signifies sacrifice, which is the calling of all believers in Christ. This is why the Roman Catholic Church calls on women to follow in the footsteps of Christ and die rather than terminate their pregnancies. In secular terms, the cross often represents a call to sacrifice one’s life in defence of one’s homeland or nation and values such as truth or freedom. The cross is therefore a symbol of death, not life, while Christianity, contrary to the claims of its apologists, seems to resemble a civilization of death rather than a civilization protecting human life and dignity.